Study guides

Q: What is 8 5 4 9 1 7 6 10 3 2 0?

Write your answer...

Submit

Related questions

100,203 in expanded form is (1 x 100000) + (0 x 10000) + (0 x 1000) + (2 x 100) + (0 x 10) + (3 x 1)(1x1,000)+(2x3) or (1 x 10^5) + (0 x 10^4) + (0 x 10^3) + (2 x 10^2) + (0 x 10^1) + (3 x 10^0)100000 + 200 + 3

0.23 = (0 x 1) . (2/10) + (3/100)

0.253 = (0 x 1) + (2/10) + (5/100) + (3/1000)

0.362 = (0 x 1) + (3/10) + (6/100) + (2/1000)

In the decimal system, the places are 10^0 (1), 10^1 (10), 10^2 (100), and 10^3 (1000) In the binary system, the places are 2^0 (1), 2^1 (2), 2^2 (4), and 2^3 (8) 1101 has one 1, one 4 and one 8. That makes 13, base ten.

0.329 =0 + 3/10 + 2/100 + 9/10000.3 + 0.02 + 0.009(0x1) + (3x1/10) + (2x1/100) + (9x1/1000)0(1) + 3(1/10) + 2(1/100) + 9(1/1000)

There are 50 ways to make $1 using Australian coins: Tries Coins 100 50 20 10 5 1 1 2 2 3 1 2 1 4 1 2 0 2 5 1 1 3 6 1 1 2 2 7 1 1 1 4 8 1 1 0 6 9 1 0 5 10 1 0 4 2 11 1 0 3 4 12 1 0 2 6 13 1 0 1 8 14 1 0 0 10 15 5 16 4 2 17 4 1 2 18 4 0 4 19 3 4 20 3 3 2 21 3 2 4 22 3 1 6 23 3 0 8 24 2 6 25 2 5 2 26 2 4 4 27 2 3 6 28 2 2 8 29 2 1 10 30 2 0 12 31 1 8 32 1 7 2 33 1 6 4 34 1 5 6 35 1 4 8 36 1 3 10 37 1 2 12 38 1 1 14 39 1 0 16 40 10 0 41 9 2 42 8 4 43 7 6 44 6 8 45 5 10 46 4 12 47 3 14 48 2 16 49 1 18 50 20

A huge number. 0 + 1 + 2 = 3 0 + 2 + 1 = 3 1 + 0 + 2 = 3 1 + 2 + 0 = 3 2 + 0 + 1 = 3 2 + 1 + 0 = 3 -0 + 1 + 2 = 3 -0 + 2 + 1 = 3 1 - 0 + 2 = 31 + 2 - 0 = 32 - 0 + 1 = 32 + 1 - 0 = 3 0 - 1 + 3 = 2 0 + 3 - 1 = 2 -1 + 0 + 3 = 2 -1 + 3 + 0 = 2 3 + 0 - 1 = 2 3 - 1 + 0 = 2 -0 - 1 + 3 = 2-0 + 3 - 1 = 2-1 - 0 + 3 = 2-1 + 3 - 0 = 23 - 0 - 1 = 23 - 1 - 0 = 2 0 - 2 + 3 = 1 0 + 3 - 2 = 1 -2 + 0 + 3 = 1 -2 + 3 + 0 = 1 3 + 0 - 2 = 1 3 - 2 + 0 = 1 -0 - 2 + 3 = 1-0 + 3 - 2 = 1-2 - 0 + 3 = 1-2 + 3 - 0 = 13 - 0 - 2 = 13 - 2 - 0 = 1 1 + 2 - 3 = 0 1 - 3 + 2 = 0 2 + 1 - 3 = 0 2 - 3 + 1 = 0 -3 + 1 + 2 = 0 -3 + 2 + 1 = 0 For each of these equations there is a counterpart in which all signs have been switched. For example 0 + 1 + 2 = 3 gives -0 - 1 - 2 = -3and so on. Now, all of the above equations has three numbers on the left and one on the right. Each can be converted to others with two numbers on each side. For example:the equation 0 + 1 + 2 = 3 gives rise to0 + 1 = 3 - 20 + 1 = -2 + 30 + 2 = 3 - 10 + 2 = -1 + 31 + 2 = 3 - 01 + 2 = -0 + 3-0 + 1 = 3 - 2-0 + 1 = -2 + 3-0 + 2 = 3 - 1-0 + 2 = -1 + 31 + 2 = 3 + 01 + 2 = +0 + 3 As you can see, the number of equations is huge!

243,090 = (2 x 100000) + (4 x 10000) + (3 x 1000) + (0 x 100) + (9 x 10) + (0 x 1) OR (2 x 10^5) + (4 x 10^4) + (3 x 10^3) + (0 x 10^2) + (9 x 10^1) + (0 x 10^0)

21000 = (2 x 10000) + (1 x 1000) + (0 x 100) + (0 x 10) + (0 x 1) OR (2 x 10^4) + (1 x 10^3) + (0 x 10^2) + (0 x 10^1) + (0 x 10^0)

(6 x 10^7) + (7 x 10^6) + (1 x 10^5) + (0 x 10^4) + (2 x 10^3) + (2 x 10^2) + (0 x 10^1) + (0 x 10^0)

1,024 = (1 x 10^3) + (0 x 10^2) + (2 x 10^1) + (4 x 10^0)

(0 x 10^0) + (0/10^1) + (0/10^2) + (7/10^3)

1*10^3 + 3*10^2 + 4*10^1 + 4*10^0.

127,803 = (1 x 10^6) + (2 x 10^5) + (7 x 10^4) + (0 x 10^3) + (8 x 10^2) + (0 x 10^1) + (3 x 10^0)

46,780.132 in expanded form using exponents = (4 x 10^4) + (6 x 10^3) + (7 x 10^2) + (8 x 10^1) + (0 x 10^0) + (1/10^1) + (3/10^2) + (2/10^3)

0=0 in binary 1=1 2=10 3=11 . . . Got it?

127,803 = (1 x 10^6) + (2 x 10^5) + (7 x 10^4) + (0 x 10^3) + (8 x 10^2) + (0 x 10^1) + (3 x 10^0)

81.402 = (8 x 10^1) + (1 x 10^0) + (4/10^1) + (0/10^2) + (2/10^3)

(1 x 10^3) + (2 x 10^2) + (5 x 10^1) + (6 x 10^0) . (2/10^1) + (4/10^2) + (9/10^3)

(1*100) + (0*10-1) + (0*10-2) + (7*10-3) + (6*10-4)

0.32 = (0 x 1) + (3/10) + (2/100) or thirty-two hundredths.

(1 x 10^6) + (0 x 10^5) + (0 x 10^4) + (0 x 10^3) + (0 x 10^2) + (0 x 10^1) + (0 x 10^0)

18,801,310 = (1 x 10^9) + (8 x 10^8) + (0 x 10^7) + (8 x 10^6) + (0 x 10^5) + (1 x 10^4) + (0 x 10^3) + (3 x 10^2) + (1 x 10^1) + (0 x 10^0)

102,436 = (1 x 10^6) + (0 x 10^5) + (2 x 10^4) + (0 x 10^3) + (4 x 10^2) + (3 x 10^1) + (6 x 10^0)